Research Progress on Supersonic Mixing Enhanced by Vortex Generators - Xie Haiwei, Zhang Dongdong, Wang Pengren, Xu Zheng, Tan Jianguo (Hangkong bingqi)
Efficient mixing of fuel and air under supersonic conditions is important for achieving efficient combustion in scramjet and combined-cycle combustion chambers. However, due to the effects of flow compression and heat release from combustion, the mixing process in supersonic flows is greatly inhibited. Vortex generators are currently the most researched and widely applied technology for mixing enhancement. According to geometric configurations, vortex generators can be categorized into lobed mixers, ramp injectors, and micro-vortex generators. In this paper, the application of lobed mixers, ramp injectors, and micro vortex generators in the field of supersonic mixing enhancement is reviewed in the order of introducing the structure and mechanism, and then introducing the research progress. Subsequently, vortex generators and other combination excitation mixing enhancement technologies, such as vortex generator-ramp induced mixing enhancement, plasma-based, and oscillating vortex generators, are introduced, and their technical prospects are pointed out, indicating their potential to achieve efficient mixing across a wide range of speeds and dynamic conditions in supersonic inflow.